LEGAL PROTECTION FOR CONSUMERS IN ELECTRONIC TRANSACTIONS IN SOCIETY - Sururi; Sri Endah Wahyuningsih; Widayati; Andi Zulfa Majida; Miftahul Janah; Saeful Bahri (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to analyze the legal protection for consumers in electronic transactions within the community. The development of information and communication technology has influenced consumption patterns with the increasing prevalence of electronic transactions. This study focuses on the legal aspects involving consumers in the context of electronic transactions, encompassing consumer rights, seller responsibilities, and relevant dispute resolution mechanisms. The research methodology involves a literature review to gain in-depth understanding of regulations and policies related to consumer protection in electronic transactions. Additionally, this study includes an analysis of legal cases related to electronic transactions involving consumers as vulnerable parties. The anticipated outcomes of this research are expected to contribute to strengthening the legal framework that safeguards consumers in electronic transactions. Practical implications of this research encompass recommendations for regulatory improvements and the enhancement of dispute resolution mechanisms, enabling consumers to engage in electronic transactions with increased confidence and protection within the community.